ANALISIS PENGELOLAAN KEUANGAN PADA CV AZURAYA PRIMA PONTIANAK - Febriani, Adeliana; Khosmas, F.Y.; Achmadi, Achmadi (Universitas Tanjungpura, 2023)
This study aims to determine Financial Management at CV Azuraya Prima Pontianak. This study discusses financial management which includes planning, recording, reporting and control. The method used is a descriptive approach method with a qualitative approach. The collection of data used is by interview and documentation. The data analysis technique in this study used a qualitative descriptive analysis. The results in this study indicate that (1) the planning that is done is the planning that is made before doing business by determining all budgets, (2) recording is done digitally using an Android-based application to record all sales and purchase transactions, (3) reports are made includes profit and loss reports that are done once a month, (4) controls used to measure the process of recording and reporting in accordance with the plans made. So it was concluded that CV Azuraya Prima must have a system of planning, recording, reporting and control in managing its finances.